2017
DOI: 10.17519/apiculture.2017.11.32.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Pollination Efficiency of Honeybees (Apis mellifera L.) and Bumblebees (Bombus terrestris L.) in Different Cultivars of Asian Pear (Pyrus pyrifolia Nakai)

Abstract: Pears (Rosaceae, Pomoideae, Pyrus) are commercially important fruits in the world, including Korea. In Korea, it represents the fifth most-grown fruit crop, after apples, persimmons, citrus fruits, grapes (Statistics Korea, 2016). Like apples, pears are self-incompatible crop and must be pollinated by different genotypes (i.e., pollinizers) for fruit set (Cho et al., 2007; RDA, 2016), and their entomophilous flowers require insect pollinators to transfer pollen (Free, 1993). However, the majority of Korean pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…This variability makes Ireland an ideal location for assessing the effects of weather on bees, and, as Irish weather is distinct from the rest of Europe, a study here could provide valuable insights as to how pollinator behaviour may change under different climate change scenarios (Sanderson et al 2015). Although the effects of weather on honeybee and bumblebee activity have been previously explored (Corbet et al 1993;Tuell and Isaacs 2010;Lee et al 2016), simultaneous observations of the two species at the colony are scant; at the time of writing, the only study on the effect of weather on pollinator activity in Ireland was made by Mahon and Hodge (2022), although this was performed at flowers, not the colony, and only within a narrow, pre-determined range of weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This variability makes Ireland an ideal location for assessing the effects of weather on bees, and, as Irish weather is distinct from the rest of Europe, a study here could provide valuable insights as to how pollinator behaviour may change under different climate change scenarios (Sanderson et al 2015). Although the effects of weather on honeybee and bumblebee activity have been previously explored (Corbet et al 1993;Tuell and Isaacs 2010;Lee et al 2016), simultaneous observations of the two species at the colony are scant; at the time of writing, the only study on the effect of weather on pollinator activity in Ireland was made by Mahon and Hodge (2022), although this was performed at flowers, not the colony, and only within a narrow, pre-determined range of weather conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Honeybees will begin to overheat and decrease activity above 40°C (Atmowidjojo et al 1997), but the highest temperature we observed was ~20°C. As seen elsewhere, bumblebee activity was little affected by changes in temperature (Lee et al 2016;Nielsen et al 2017), though this could again be a limitation of the temperatures observed as temperatures over ~27°C are associated with negative effects on this species (Kenna, Pawar & Gill 2021); if higher temperature conditions were recorded, we might have detected a stronger effect of temperature on bumblebees.…”
Section: Temperaturementioning
confidence: 65%
“…In our study it appears the activity of bumblebees in less sunny, windier, and more humid conditions may compensate for low honeybee activity at such times, a phenomenon known as functional complementarity (Boyle-Makowski & Philogène 1985;Kühsel & Blüthgen 2015;Lee et al 2016). We assume that a subset of all bees returning to and leaving a colony are foraging for floral resources, and, therefore, pollinating flowers (Corbet et al 1993); our results illustrate how bee diversity can be important for ensuring pollination services in contemporary variable weather conditions.…”
Section: Pollination Services In the Current Climatementioning
confidence: 72%
See 2 more Smart Citations